IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK PESERTA DIDIK - Awaliah Rizki Nurfadhilah (UNISAN JURNAL, 2024)
Implementation of counseling guidance in the moral development of students is an educational process that focuses on changing the character and behavior of students to behave well and have good character. Implementation of counseling guidance in moral development for students at SD IT Qurratu A’yun Liluwo Kec. Kota Tengah Kota Gorontalo has done well. Guidance and Counseling is an integral activity that cannot be separated. The word Guidance (Guidance) is always coupled with Counseling as a compound word, Counseling which is one of the Guidance techniques is often said to be the core of the whole service and Guidance Data collection methods are carried out using observation, interviews and documentation. In the analysis, data reduction steps were carried out. As for analyzing with inductive thinking. Based on the data obtained, the results of research on the implementation of counseling guidance in the moral development of students show a fairly good and significant level of change, seen from students always following counseling guidance and moral development using the methods of understanding, advice, motivation, advice and habituation. So that it can slowly change the nature and habits of students for the better.